Antibiotic resistance and polymorphism in the quinolone resistance-determining region of Campylobacter spp. isolated from 1-day-old ducklings. (May 2016) - Hamed, Engy A.; AbdelRahman, Mona A.A.; Shalaby, Azhar G.; Morsy, Mai M.; Nasef, Soad A.
Highlights: Thirty-six Campylobacter coli and Campylobacter jejuni isolates were recovered from 1-day-old ducklings. Most isolates were sensitive to chloramphenicol, tetracycline and erythromycin. Resistance to ofloxacin and trimethoprim SXT was very high. tet (O) gene was detected in 9/33 C.   coli isolates. gyr A gene in 12 isolates was similar to strains recovered from poultry and humans in Eurasia. Graphical Abstract: Abstract: Thirty-three isolates of Campylobacter coli and three isolates of Campylobacter jejuni were recovered from 150 1-day-old ducklings . All isolates were sensitive to chloramphenicol and amikacin, but resistant to sulfamethoxazole-trimethoprim (SXT) by the disc diffusion method. Most isolates were susceptible to tetracycline and erythromycin, but resistant to ofloxacin and ciprofloxacin. Of the 33 C. coli isolates, nine were positive for the tetracycline resistance gene tet(O), although only two of these were resistant to tetracycline in the disc diffusion test. None of the isolates possessed mutations in the quinolone resistance-determining region ( QRDR ) of the gyrA gene infrequently linked to FQ-resistance. The finding indicated that ducklings may be a source of antibiotic resistant Campylobacter spp. with potential poultry and public health hazard.